2015
DOI: 10.1177/0021998315596594
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of symmetric and asymmetric glass fiber reinforced plastic laminates subjected to low-velocity impact

Abstract: Low-velocity impact induced damage in symmetric and asymmetric laminates is analyzed. A generalized lay-up sequence is proposed for asymmetric laminate. Asymmetric laminate fabricated according to the proposed lay-up sequence have its stiffness characteristic almost identical to those of a symmetric laminates. Proposed lay-up sequence provides a laminate which have zero bending-extension coupling and behaves as quasi-isotropic laminate. A cylindrical impactor with hemispherical nose having mass 5.23 kg is impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Singh et al. [35] have reported that quasi-isotropic symmetric and asymmetric GFRP laminates are having corresponding absorb energy of 59.7 J and 45.98 J which are higher than that of laminates suggested by various researchers.…”
Section: Introductionmentioning
confidence: 90%
“…Singh et al. [35] have reported that quasi-isotropic symmetric and asymmetric GFRP laminates are having corresponding absorb energy of 59.7 J and 45.98 J which are higher than that of laminates suggested by various researchers.…”
Section: Introductionmentioning
confidence: 90%
“…The proposed quasi-isotropic symmetric laminate 41 with stacking sequence of [(0 , 90 )/(þ45 , À45 )/ (þ45 , À45 )/(90 , 0 )] S and 280 Â 280 mm 2 dimension was prepared by Vacuum Assisted Hand Layup Technique Method (VAHLTM). The magnitude in the parenthesis represents warp and weft directions of the fibres running through each ply.…”
Section: Laminate Preparationmentioning
confidence: 99%
“…Menna et al., 4 Chandekar et al., 5 Singh et al. 6 studied the composite specimens which were subjected to impact loading. Specimens were analyzed with increasing impact energy under low-velocity impact loading using LS-DYNA and the results were compared with experimental analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As it was seen for both of the studies that the numerical results were in good agreement with experimental results, there have been quite some studies about glass fiber composites to understand the low-velocity impact behavior. Menna et al, 4 Chandekar et al, 5 Singh et al 6 studied the composite specimens which were subjected to impact loading. Specimens were analyzed with increasing impact energy under low-velocity impact loading using LS-DYNA and the results were compared with experimental analysis.…”
Section: Introductionmentioning
confidence: 99%